Hydrothermal Synthesis: Low−Temperature Subcritical Water for Ceria−Zirconia Mixed Oxides Preparation - Siti Machmudah; Widiyastuti Widiyastuti; Wahyudiono Wahyudiono; Sugeng Winardi; Hideki Kanda; Motonobu Goto (Universitas Gadjah Mada, 2021)
A low-temperature hydrothermal synthesis technique was employed as a medium to produce ceria−zirconia mixed oxides particles at temperatures of 200–300 °C and pressure of 10 MPa in a batch process. At these conditions, the average crystallite sizes of ceria−zirconia mixed oxides increased slightly with increasing reaction temperature when the feed solution containing ceria and zirconia with a ratio of 1:1 was fed. SEM images illustrated that the morphologies of the ceria−zirconia mixed oxides particles were spherical and spherical−like with a diameter of around 100 nm. The EDX spectrum indicated that the signal corresponding to the ceria and the zirconia elements at 5 and 2 keV, respectively, were strongly detected in the products. The XRD pattern revealed that the mixed metal oxides particle products that comprised of cerium and zirconium oxides particles with cubic and monoclinic structures, respectively, were affected by their molar content in the feed solution.